A Static-99R Validation Study on Individuals With Mental Disorders: 5 to 20 Years of Fixed Follow-Up After Sexual Offenses - Christian Baudin; Christian Baudin; Thomas Nilsson; Thomas Nilsson; Thomas Nilsson; Joakim Sturup; Joakim Sturup; Märta Wallinius; Märta Wallinius; Märta Wallinius; Peter Andiné; Peter Andiné; et al. (Frontiers in Psychology, 2021)
‘The Static-99R is one of the most commonly used risk assessment instruments for individuals convicted of sexual offenses. It has been validated for use on many populations, but few studies specifically target and describe individuals with mental disorders. Additionally, research on the discriminative properties (how well the instrument separates recidivists from non-recidivists) of the instrument over longer follow-up periods is scarce. This article evaluated the validity of the Static-99R using a cohort of individuals with mental disorders convicted of sexual offenses in Sweden (N = 146) with fixed 5-year (n = 100), 10-year (n = 91), 15-year (n = 79), and 20-year (n = 36) follow-up periods. A Static-99R cut score of 6 demonstrated the highest Youden index, maximizing sensitivity (72.7%) and specificity (74.2%), with 25.8% of recidivists correctly assumed to reoffend sexually and 95.7% of non-recidivists correctly assumed not to. The Static-99R instrument demonstrated adequate discrimination (AUC = 0.79, CI 95% = 0.70–0.87, and OR = 1.45, CI 95% = 1.14–1.84, p < 0.001, 5-year fixed follow-up), with only marginal differences for 10-, 15-, and 20-year fixed follow-up (AUC = 0.73, 0.74, and 0.74 and OR = 1.31, 1.36, and 1.40, respectively). Calibration (quantifying risk and correspondence with the instrument’s norms) was acceptable (Brier = 0.088, P/E = 0.70, E/O = 1.43), with the routine sample norms displaying a decisively better fit to the study cohort compared to the high-risk/high-need sample norms. The results affirm the recommendation that, when in doubt and where there is no recent local norm group large enough available, the Static-99R routine sample found in the evaluators’ workbook should be used.